Household interaction and the labor supply of married women - Zvi Eckstein; Osnat Lifshitz (Institute for the Study of Labor (IZA), 2012)
Changing social norms, as reflected in the interactions between spouses, are hypothesized to affect the employment rates of married women. A model is built in order to estimate this effect, in which the employment of married men and women is the outcome of an internal household game. The type of the household game is exogenously determined as either Classical or Modern. In the former type of household, the spouses play a Stackelberg leader game in which the wife's labor supply decision is based on her husband's employment outcome while the latter type of household is characterized by a symmetric and simultaneous game that determines the spouses' joint labor supply as Nash equilibrium. Females in Modern households are predicted to have higher employment rates than women in Classical households if they have narrower labor market opportunities and/or higher relative risk aversion. The household type is exogenously determined when the couple gets married and is treated as unobserved heterogeneity. The model is estimated using the Simulated Moments Method (SMM) and data from the Panel Study of Income Dynamics (PSID) survey for the years 1983-93. The estimated model provides a good fit to the trends in employment rates and wages. We estimate that 38 percent of households are Modern and that the participation rate of women in those households is almost 80 percent, which is about 10 higher than in Classical households. Meanwhile, the employment rate among men is almost identical in the two types of household.
Keywords: E24; J2; J3; 330; dynamic discrete choice; household labor supply; household game; Weibliche Arbeitskräfte; Arbeitsangebot; Ehe; Haushaltsökonomik; Spieltheorie; Schätzung; USA